The State of the Art in Colorectal Cancer Molecular Biomarker Testing. (March 2016) - Pillai, Raju K.; Lopategui, Jean R.; Dhall, Deepti; Guindi, Maha; Slavin, Thomas; Lofton-Day, Catherine E.; Patterson, Scott D.
Abstract : The number of molecular biomarkers to inform treatment decisions in patients with metastatic colorectal cancer (mCRC) continues to expand and with it the methodologies that can be employed to evaluate these biomarkers. Beyond standard diagnostic and prognostic biomarkers, such as those used for Lynch syndrome, mutations in KRAS exon 2 are well established as predictive for lack of response to the antiepidermal growth factor receptor therapies panitumumab and cetuximab. Recent studies have extended these findings by demonstrating that mutations in KRAS exons 3 and 4 and in NRAS exons 2, 3, and 4 (with all KRAS and NRAS mutations collectively referred to as RAS ) are also predictive for treatment outcomes among patients with mCRC receiving panitumumab and cetuximab in combination with chemotherapy or as monotherapy. Consequently, evaluation of these additional loci has been incorporated into current clinical guidelines, and pathologists will need to develop testing procedures and algorithms to reliably and rapidly evaluate RAS status. With the increased number of mutations that must be examined to evaluate the status of RAS and other emerging biomarkers, next-generation sequencing technologies are likely to become increasingly important in mCRC testing. This review describes new considerations for pathologists that have arisen as a consequence of the incorporation of additional biomarker testing into clinical practice for mCRC.